MEMAHAMI GERAKAN FEMINIS: BUTUH KEJELIAN - Abubakar, Istiâ€™anah (EGALITA, 2007)
Women historically have been a subject of talk and discussion about their existences and their role. Both aspects are the most interesting topics to be discussed. To feminist movement, gender equity is a sort of women struggle in order they are respected. However, we should realize that the source (root) of women problem is not the matter of oppression, violence or marginalization but it is more on womenâ€™s mentality or feeling which influences people to consider that women experience that aforementioned problems. Furthermore, the assumption on womenâ€™s problem is supported by recent social phenomena which are global as suggested by Paloma Picasso, â€œThe world has becoming more and more cosmopolitan and we are all influencing each otherâ€.